Ambiguity revealed - Ralph-C. Bayer; Subir Bose; Matthew Polisson; Ludovic Renou (Institute for Fiscal Studies (IFS), 2013)
We derive necessary and sufficient conditions for data sets composed of state-contingent prices and consumption to be consistent with two prominent models of decision making under uncertainty: variational preferences and smooth ambiguity. The revealed preference conditions for subjective expected utility, maxmin expected utility, and multiplier preferences are characterised as special cases. We implement our tests on data from a portfolio choice experiment.
Keywords: D1; D8; 330; ambiguity; expected utility; maxmin; revealed preference; smooth; uncertainty; variational